If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(5) = 5 + -5 Reorder the terms for easier multiplication: 5f = 5 + -5 Combine like terms: 5 + -5 = 0 5f = 0 Solving 5f = 0 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by '5'. f = 0 Simplifying f = 0
| 17f+2=4f | | .5(8a+12)-27=15 | | p/8-1=7p/6+2 | | 40-2x=130-22x | | -3b+5b=2(2-b)+6(b-2) | | 4w+8=88 | | +2=7 | | (9x^4-6x^2+1)-(x^4-12x^3+34x^2+12x+1)=0 | | 2660+x(175.75)=5999.25 | | 72-x=86-2x | | -9+-5+14+-6= | | 5q+8=11 | | 2(3x+4y)=4x+2y | | 180-36-x=102 | | (13x-1)= | | 6+-4+-9+7= | | 0-8b=12 | | 4w+5z=6 | | 10x-1=1-4x | | 6y=5x+3 | | 3b+5b=2(2-b)+6(b-2) | | 3x-24=2x+35 | | 1.4x-0.9=33 | | (10x+29)= | | 5(y+4)=-8y-45 | | 6+2=14-x | | 315+15p=450 | | 8x-6-3x=4 | | -x+3y-4z=-15 | | 200p+40p=350+50p | | 14=n+2 | | 6-4t=10 |